Long-Term Alteration of Reactive Oxygen Species Led to Multidrug Resistance in MCF-7 Cells. (12th December 2016) - Cen, Juan; Zhang, Li; Liu, Fangfang; Zhang, Feng; Ji, Bian-Sheng
Abstract : Reactive oxygen species (ROS) play an important role in multidrug resistance (MDR). This study aimed to investigate the effects of long-term ROS alteration on MDR in MCF-7 cells and to explore its underlying mechanism. Our study showed both long-term treatments of H2 O2 and glutathione (GSH) led to MDR with suppressed iROS levels in MCF-7 cells. Moreover, the MDR cells induced by 0.1  μ M H2 O2 treatment for 20 weeks (MCF-7/ROS cells) had a higher viability and proliferative ability than the control MCF-7 cells. MCF-7/ROS cells also showed higher activity or content of intracellular antioxidants like glutathione peroxidase (GPx), GSH, superoxide dismutase (SOD), and catalase (CAT). Importantly, MCF-7/ROS cells were characterized by overexpression of MDR-related protein 1 (MRP1) and P-glycoprotein (P-gp), as well as their regulators NF-E2-related factor 2 (Nrf2), hypoxia-inducible factor 1 (HIF-1 α ), and the activation of PI3K/Akt pathway in upstream. Moreover, several typical MDR mediators, including glutathione S-transferase- π (GST- π ) and c-Myc and Protein Kinase C α (PKC α ), were also found to be upregulated in MCF-7/ROS cells. Collectively, our results suggest that ROS may be critical in the generation of MDR, which may provide new insights into understanding of mechanisms of MDR.